Construction of a highly error-prone DNA polymerase for developing organelle mutation systems. Issue 21 (2nd November 2020) - Ji, Junwei; Day, Anil
Abstract: A novel family of DNA polymerases replicates organelle genomes in a wide distribution of taxa encompassing plants and protozoans. Making error-prone mutator versions of gamma DNA polymerases revolutionised our understanding of animal mitochondrial genomes but similar advances have not been made for the organelle DNA polymerases present in plant mitochondria and chloroplasts. We tested the fidelities of error prone tobacco organelle DNA polymerases using a novel positive selection method involving replication of the phage lambda cI repressor gene. Unlike gamma DNA polymerases, ablation of 3′–5′ exonuclease function resulted in a modest 5–8-fold error rate increase. Combining exonuclease deficiency with a polymerisation domain substitution raised the organelle DNA polymerase error rate by 140-fold relative to the wild type enzyme. This high error rate compares favourably with error-rates of mutator versions of animal gamma DNA polymerases. The error prone organelle DNA polymerase introduced mutations at multiple locations ranging from two to seven sites in half of the mutant cI genes studied. Single base substitutions predominated including frequent A:A (template: dNMP) mispairings. High error rate and semi-dominance to the wild type enzyme in vitro make the error prone organelle DNA polymerase suitable for elevating mutation rates in chloroplasts and mitochondria.